A Randomized Controlled Trial Of Contingency Management Therapy In Enhancing Treatment Engagement In A Drug Rehabilitation Centre - Mohamad Salleh Abdul Ghani; Haslee Sharil Lim Abdullah; Mohamad Isa Amat; Mohd Khairul Anuar Rahimi; Muhammad Khairi Mahyuddin (Center for Promoting Ideas, USA, 2024)
Indexed by ERA